An integrated approach to add value to acerola fruit (Malphigia emarginata): antioxidant extraction and its performance in food emulsion - Loro, Ana Carolina (2020)
Antioxidants have the ability to protect, prevent, or reduce the damage caused by the phenomena of oxidation due to free radicals\' activity. They play a key role in the defense mechanisms of plants and other biological systems, acting directly in the early stages of generation and propagation of free radicals in the oxidative process, in both food and biological systems. In foods, they act by preventing and/or delaying the processes of lipid autoxidation through the neutralization of free radicals. Autoxidation lead to the development of undesirable flavors and chemical compounds in food, besides deterioration of quality and shortening the shelf life of food products. The use of antioxidant compounds is a necessity in the food industry, which normally uses synthetic products. The questioning of the innocuity of synthetic antioxidants and the recent demand for natural ingredients by consumers have motivated the study of alternative sources and their processing parameters for food application. Attention has been given to ascorbic acid, tocopherols, and carotenoids that present known potential for food application. Acerola fruits (Malphigia emarginata DC.) are an important source of natural antioxidants, due to the high levels of ascorbic acid and phenolic compounds. In this work natural extracts obtained from acerola pulp and seeds were applied in lipid matrices. The study consisted of three stages: extraction conditions determination using experimental design and optimization methods; oxidative stability study in lipid system models comparing natural extracts to synthetic ones; and sensorial evaluation of emulsions added off natural antioxidants. The results evidenced a high antioxidant capacity of extracts obtained under optimized conditions and a significant antioxidant action in the oxidative stability in lipid systems. In addition, it was observed high sensorial acceptance and low sensorial profile differentiation of emulsions added of natural extracts in comparison to the synthetic antioxidants. Therefore, acerola is an efficient substitute for synthetic antioxidants in lipid-based foods without causing sensorial alteration.